2020
DOI: 10.1186/s10033-020-00453-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural Stress–Fatigue Life Curve Improvement of Spot Welding Based on Quasi-Newton Method

Abstract: Abstract∆F-N curves are usually used to predict the fatigue life of spot welding in engineering, but they are time-consuming and laborious and not universal. For the purpose of predicting the fatigue life of spot welding accurately and efficiently, tensile–shear fatigue tests were conducted to obtain the fatigue life of spot-welded specimens with different sheet thicknesses combinations. These specimens were simulated by using the finite element method, and the structural stress was theoretically calculated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Qin. Y. et al [9] have reported the use of beam elements to model the weld nugget during the fatigue simulation of spot welded joints. In all of the mentioned works, no attempts have been made to analysis the stiffness anisotropy in fatigue life simulation of self-piercing riveted components.…”
Section: State Of the Artmentioning
confidence: 99%
“…Qin. Y. et al [9] have reported the use of beam elements to model the weld nugget during the fatigue simulation of spot welded joints. In all of the mentioned works, no attempts have been made to analysis the stiffness anisotropy in fatigue life simulation of self-piercing riveted components.…”
Section: State Of the Artmentioning
confidence: 99%
“…The cold-rolled 301L plate is a metastable austenitic stainless steel containing less chromium and nickel and adding austenitizing element nitrogen, which is the main material used in the manufacturing of railway light stainless steel passenger cars [1,2]. Owing to the different amounts of strain-induced martensite transformed in the cold rolling process, the yield strength of cold-rolled plates ranges from 200 MPa to 700 MPa, which determines that the welding methods used in the manufacturing of vehicles are resistance spot welding and laser welding with concentrated heat input to reduce the deterioration of the mechanical properties of cold-rolled plates caused by welding heat [3,4]. Penetration and nonpenetration laser welded lap joints are common joining methods in rail passenger cars, and the non-penetration laser lap welding is an assembling method for side facade panels of passenger cars, which can not only improve corrosion resistance but also provide vehicle bodies with a weld-free appearance [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Cold rolled 301L plate is a metastable austenitic stainless steel containing less chromium and nickel and adding austenitizing element nitrogen, which is the main material used in the manufacture of railway light stainless steel passenger cars. Due to the different amount of strain-induced martensite transformed in the cold rolling process, the yield strength of cold-rolled plates ranges from 200 MPa to 700 MPa, which determines that the welding methods used in the vehicle manufacture are resistance spot welding and laser welding with concentrated heat input to reduce the deterioration of the mechanical properties of cold-rolled plates caused by welding heat [1][2][3][4]. The penetration and non-penetration laser welded lap joints are common joining method in rail passenger cars, and the non-penetration laser lap welding is an assembling method for side facade panels of passenger cars, which can not only improve corrosion resistances but also provide vehicle body with a weld-free appearance [5].…”
Section: Introductionmentioning
confidence: 99%